FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN GANGGUAN FUNGSI PARU PADA PEKERJA DI UNIT BOILER INDUSTRI TEKSTIL X KABUPATEN SEMARANG - Ellita Ersa Afiani; Siswi Jayanti; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
One of the negative impacts of boiler operation using coal fuel is air pollution caused by coal dust. Respirable coal dust can risk workers of lung function disturbance either restriction, obstruction or mixed. The purpose of this study was analyze factors associated with lung function disturbance to workers in boiler unit of X textile industry in Semarang district. This research was an observational research with cross sectional approach. The subjects were all 35 workers in boiler unit. The measurement result of respirable coal dust level showed that the respirable coal dust level above the Threshold Limit Value (TLV) was 2 mg/m3. The result of this study indicates that lung function disturbance which occurs to workers in boiler unit is a mild restrictive lung disease which of the 35 subjects, 34.3% of them had mild restriction. Based on the Fisher Excat Test correlation test, researchers concluded that ages is not associated with lung function disturbance (p-value = 0,726), history of lung disease related to lung function disturbance (p-value = 0,003), there is no correlation between working periode with lung function disturbance (p-value = 1,000), type of work associated with lung function disturbance (p-value = 0,013), there is no correlation between nutritional status with lung function disturbance (p-value = 1,000), personal protective equipment related to lung function disturbance (p-value = 0,024). Researchers suggested that the workers always use mask when he work and replace the mask every day or at least wash fabric mask every day .